Following disease progression in motor neuron disorders with 3 motor unit number estimation methods. Issue 1 (29th November 2018) - Jacobsen, Anna Bystrup; Bostock, Hugh; Tankisi, Hatice
ABSTRACT: Introduction: The objective of this study was to evaluate a recently developed motor unit number estimation (MUNE) method, MScanFit MUNE (MScan), as a measure of disease progression in amyotrophic lateral sclerosis (ALS) compared with compound muscle action potential (CMAP) amplitude and 2 traditional MUNE methods. Methods: ALS patients were evaluated clinically using the ALS Functional Rating Scale—Revised (ALSFRS‐R). MScan, multiple‐point stimulation MUNE (MPS), and motor unit number index (MUNIX) were performed in the abductor pollicis brevis (APB) muscle at baseline (27 patients), 4 months (23 patients), and 8 months (16 patients). Results: Of the 5 measures, MScan registered the largest decline (8.7% per month), compared with MPS (3.4%), MUNIX (4.8%), CMAP amplitude (2.0%), and ALSFRS‐R (1.9%). Only MScan and ALSFRS‐R registered significant decrements over 4 and 8 months. Discussion: MScan may be useful as a sensitive, objective tool for quantifying motor unit loss in ALS. Muscle Nerve 59 :82–87, 2019